L-Lactate Electrochemical Biosensor Based on an Integrated Supramolecular Architecture of Multiwalled Carbon Nanotubes Functionalized with Avidin and a Recombinant Biotinylated Lactate Oxidase - Tamborelli, Luis Alejandro (2024)
L-Lactate is an important bioanalyte in the food industry, biotechnology, and human healthcare. In this work, we report the development of a new L-lactate electrochemical biosensor based on the use of multiwalled carbon nanotubes non-covalently functionalized with avidin (MWCNT-Av) deposited at glassy carbon electrodes (GCEs) as anchoring sites for the bioaffinity-based immobilization of a new recombinant biotinylated lactate oxidase (bLOx) produced in Escherichia coli through in vivo biotinylation. The specific binding of MWCNT-Av to bLOx was characterized by amperometry, surface plasmon resonance (SPR), and electrochemical impedance spectroscopy (EIS). The amperometric detection of L-lactate was performed at −0.100 V, with a linear range between 100 and 700 µM, a detection limit of 33 µM, and a quantification limit of 100 µM. The proposed biosensor (GCE/MWCNT-Av/bLOx) showed a reproducibility of 6.0% and it was successfully used for determining L-lactate in food and enriched serum samples.